PRE-FORMULATION STUDIES OF PAPAYA (C.PAW-PAW) EXTRACT TO USE FOR TABLET PREPARATION - Kushwah, Mahendra Singh Kushwah; Kumar, Mr. Manoj (International Journal of Multidisciplinary Research and Studies, 2021)
An object is to studies on the pharmacological conditioning of papaya (c. paw-paw) and bay splint parade that these shops effectively palliate degenerative conditions including diabetes. Still, herbal medicines from papaya and bay splint have no-way been made. The end of this exploration was to formulate a tablet from the combination of papaya excerpt and bay splint with different attention (1, 2, and 3) of polyvinyl pyrro lidone (PVP) K30 as a binder using the wet granulation system. (18)